Analysis of Gen Z’s Interaction with Digital Voice Assistant using TAM Approach - Wijayanti, Nova Indah; Putri, Donna Benitya; Salindeho , Vanesa Gabriela (Media Komunikasi FPIPS, 2024)
This study aims to investigate Generation Z's readiness to utilize new technology in the field of Digital Voice Assistants for application to hotel services. This research employs a descriptive approach with a quantitative methodology, utilizing a survey method to assess the optimization of Digital Voice Assistants among Generation Z. The analysis was conducted based on three concepts of the Technology Acceptance Model (TAM), which encompasses four indicators: perceived usefulness, perceived ease of use, attitude towards use, and behavioral intention. The results indicated that perceived usefulness had a mean score of 3.9, perceived ease of use had a mean score of 3.8, attitude toward use had a mean score of 3.8, and behavioral intention had a mean score of 3.5, suggesting that all indicators demonstrated high scores based on reference values. The implications of this research suggest that Generation Z can accept DVA technology for potential implementation in hotel services.